KORELASI ANTARA KECERDASAN EMOSIONAL DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR TEMATIK SISWA KELAS IV SDN - Indah Cahyana; Kartono Kartono; Rio Pranata (Universitas Tanjungpura, 2022)
AbstractThis study aims to describe the level of relationship between emotional intelligence and learning motivation with thematic learning outcomes of fourth grade students at SDN 37 Southeast Pontianak. The method used in this research is a descriptive method with a correlational study. The population in this study were all fourth grade students at SDN 37 Southeast Pontianak. Sampling using a simple random sampling technique with a total sample of 30 students of class IV SDN 37 Southeast Pontianak. The data collection technique used in this study is indirect communication techniques and documentary study techniques. The results showed that the average emotional intelligence was 82.13, the average learning motivation was 82.63, and student learning outcomes got an average score of 80.40. Based on Statistical analysis uses the multiple correlation formula to calculate correlation between motivation and emotional intelligence with student learning outcomes, r count is 0.649, and r table is 0.361, this means r count > r table or (0.649 > 0.361). It can be concluded that there is a strong relationship between emotional intelligence and learning motivation with thematic learning outcomes of fourth grade students at SDN 37 Southeast Pontianak.Keywords: Correlation, Emotional Intelligence, Learning Outcomes, Motivation